Medición penal en delitos de hurto como solución alternativa al proceso penal en el Ecuador - Vallejo Echeverría, Alexandra Estefanía (2015)
The present paper is based on the introduction to the process of mediation as an alternative method to solve conflicts within the criminal code legislation, with regard to theft felony. The Constitution of the Republic from 2008 acknowledges arbitration and mediation as methods to solve conflicts; at the same time, the new “Código Orgánico Integral Penal”, which was activated in 2014, makes reference to penal conciliation in the case of minor offences and also offers the possibility of making a deal in the case that the imprisonment is less than 5 years; in that case that there are no fatal accidents in transit issues, and; felonies against property do not exceed thirty minimum wages. The penal conciliation that offers the “COIP”, differs from the mediation method, in that conciliation offers two opportunities within the process of achieving an agreement among the people involved in the trial, but, this does not necessarily offer a guarantee of being fair to the people involved; and in mediation there exists a big possibility of reaching a fair and equitable agreement for both parties with the help of a specialized third person who is impartial and neutral; this person will direct the conversation and communication between them and he-she will look after the best interest of each of the people so they may find the best solution for their conflicts. Thus, mediation focuses on the win-win since the victim, as well as the accused, through dialogue, will be the only ones capable of solving their disagreements and achieving a fast solution without going to trial.